PRESENT TECHNIQUES FOR SPATIOTEMPORAL ANALYSIS OF EARTH DEFORMATIONS USING DINSAR AND GNSS: PRESENT TECHNIQUES FOR SPATIOTEMPORAL ANALYSIS OF EARTH DEFORMATIONS USING DINSAR AND GNSS - Petrova, Vesela (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2025)
One of the significant problems facing Earth sciences is the quantitative description and analysis of the dynamics of the Earth’s surface. A key requirement in solving this fundamental question is the precise determination of the displacements and deformations caused by various geodynamic processes of natural or anthropogenic origin. In recent decades, Earth observation has become widely used in disaster risk management – including preparedness, response, recovery and mitigation. Its role in disaster response is particularly valuable, as it provides critical information for researchers and decision-makers. Earth observation is the collection of data about the planet through remote sensing technologies, which are often complemented by ground-based surveys. This approach has fundamentally changed the way we perceive the world, enabling timely and accurate mapping and monitoring of phenomena on a large scale. An established method for continuous monitoring of earth deformations is the use of data from active radar remote sensing. Synthetic Aperture Radar (SAR) provides information that serves as the basis for the construction of interferometric images (IFIs) by quantifying the displacements of the Earth’s surface within a specified time interval using the technique of differential radar interferometry (DInSAR) by analysing the phase differences between radar images taken at different times.